Evaluation of Neurosurgery Consultations in Hospitalized Geriatric Patients During and After the COVID-19 Pandemic - Hakan Kina; Hakan Yavuzer (Medicina)
Background and Objectives: This study aims to evaluate neurosurgery consultations for elderly patients during and following the COVID-19 pandemic. Materials and Methods: This study included patients aged 65 and older who were hospitalized in non-neurosurgery departments at Istinye University Gaziosmanpasa Medical Park Hospital and were referred for neurosurgery consultations between 1 April 2020 and 31 May 2024. Patients in the intensive care unit and emergency department were excluded. The period from 1 April 2020 to 30 April 2022 was defined as the pandemic period, and from 1 May 2022 to 31 May 2024 as the post-pandemic period. Results: A total of 123 patients were included in this study, with 57 from the pandemic period and 66 from the post-pandemic period. The average age during the pandemic period was 73.45 years (range: 65–93), compared to 71.09 years (range: 65–94) in the post-pandemic period. During the pandemic, 26.3% of patients were recommended for physical therapy and rehabilitation, 24.6% were advised to undergo surgery, 19.3% received neurology consultations, and 17.5% received medical treatment. In the post-pandemic period, 37.9% were recommended for surgery, 16.7% for neurology, 13.6% for physical therapy and rehabilitation, and 7.6% for medical treatment. Overall, 56.4% of patients accepted surgery. Conclusions: Despite the high prevalence of comorbidities in geriatric patients, appropriate neurosurgical referrals significantly improve treatment success, enhance quality of life and mobility, and reduce mortality. We therefore recommend earlier and more attentive referrals to neurosurgery for elderly patients with relevant symptoms to facilitate timely and effective interventions.